Der modale Infinitiv in der modernen russischen Standardsprache - Maurice, Florence (Slavistische Beitraege, 1996)
The basis of this work is a corpus of approximately 1300 sample sentences, mostly taken from literary sources (mainly: Amfiteatrov, Bulgakov, Čechov, Dostoevskij, Il'f / Petrov, Grin, Rybakov, Zoščenko, etc.). Furthermore, comics were evaluated, since I assumed that they can be found more colloquialisms, but their frequency is higher in "Mickey Mouse" than "Tim and Struppi". In addition, journalistic texts (Argumenty i fakty, Literaturnaja Gazeta, Krokodil, Ogonek) and the texts of Russkaja razgovornaja reč (1978) were used.